The training of early childhood teachers through research with children: an orientation for the reflection on the early childhood teachers training. - Pedro, A. (2012)
In this article, we present some reflections on great challenges that are currently placed to the training of early childhood teachers and teachers in general. In order to do so, we shall use the theoretical referentials which use the principle of reflection on practice as the strutucturing axis of the training and that defend that research can frame and guide that reflection. The great challenges of education enunciated by Morin, by the humanistic focus that they have, gather some consensus and appeal to the necessity of professionals able to think in contents and in educational processes bearing in mind notions such as: complexity, contextualization, interdisciplinarity, uncertainty, identity, understanding, autonomy, participation and citizenship. All of these notions lead us towards a professional identity which cannot be built if framed into technical rationality paradigms. On the other hand, the recognition of the individual and collective agency of the children (Corsaro) puts in evidence their competence and reveals the need to deconstruct ideas and representations (conceptions) that work as truth regimes (Foucault) in Early Childhood Education, thus defying the training to find strategies that support the personal exercise of deconstruction. The experience of research-action-training that we are presenting, which was undertaken during the initial training of early childhood teachers, aimed at supporting the processes of reflection and deconstruction and, simultaneously, the development of pedagogical practices which paid attention to the knowledge enunciated by Morin, having as an assumption that the Early Childhood Education is the first step of the basic education, a space and a time where educational intentions are at stake.